Effects of ticagrelor pretreatment on electrophysiological properties of stellate ganglion neurons following myocardial infarction. (16th August 2020) - Cheng, Lijun; Fu, Huaying; Wang, Xinghua; Ye, Lan; Lakhani, Ishan; Tse, Gary; Zhang, Zhiwei; Liu, Tong; Li, Guangping
Abstract: Higher sympathetic activity predisposes to malignant ventricular arrhythmias in the context of myocardial infarction (MI). This is, in part, mediated by the electrical activity of the stellate ganglion (SG). The aim of this study is to examine the effects of ticagrelor pretreatment on the electrophysiological properties of SG neurons following MI in rabbits. MI was induced by isoproterenol (ISO) of 150 mg kg ‐1 d ‐1 (twice at an interval of 24 hours). Ticagrelor pretreatment was administered at low‐ (10 mg kg ‐1 d ‐1 ) or high‐dose (20 mg kg ‐1 d ‐1 ). Protein and RNA expression were determined by immunohistochemical analysis and real‐time PCR, respectively. The activity of sodium channel current ( I Na ), delayed rectifier potassium current ( I KDR ), M‐type potassium current ( I KM ) as well as action potentials (APs) from SG neurons were measured by whole‐cell patch‐clamp. Intracellular calcium concentrations were measured by confocal microscopy. Compared with the control group, the MI group exhibited a greater amplitude of I Na, I KDR and I KM, significantly altered activation and inactivation characteristics of I Na, no significant alterations in protein or mRNA expression of sodium and M‐type potassium channels, along with higher AP amplitude and frequency and intracellular calcium concentrations. Most of these abnormalities were prevented by pretreatment with low‐ or high‐dose ticagrelor. Our data suggest that ticagrelor exerts cardioprotective effects, potentially through modulating the activity of different ion channels in SG neurons. Abstract : Increased SG activity has been implicated in the pathogenesis of various cardiovascular diseases. Myocardial infarction (MI) can lead to increased activity of the sympathetic efferent nerves through electrophysiological remodelling of the SG. Our results confirmed that neuronal activity was enhanced following MI in the SG through increases in the activity of sodium and potassium channels, also ticagrelor exerts cardioprotective effects, potentially through modulating the activity of different ion channels in SG neurons.